2021
DOI: 10.1590/1980-220x-reeusp-2021-0104
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene by the nursing team in home care: a cross-sectional study

Abstract: Objective: to identify whether nursing professionals carry out hand hygiene, how they do it, and what resources are available for this practice during home visits. Method: cross-sectional study conducted in a public Home Care service. The World Health Organization instrument was used to observe the hand hygiene technique, the time of performance, and the product used. Results: a total of 940 hand hygiene opportunities taking place in 231 home visits were observed. Overall adherence was 14.4%, with the practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 12 publications
(13 reference statements)
0
1
0
3
Order By: Relevance
“…Smith et al concluded that the average hand hygiene compliance rate of staff in long-term care facilities is only about 14.7% [6]. Similar results were found by Cordeiro et al, with an average hand hygiene compliance rate of 14.4%, varying with 4.8% before patient contact and 53.7% after patient contact, among other differentiation aspects [7]. Assuming these ndings, Assab and Temime (2016) incorporated real data on the spread of the Norovirus into a mathematical model, demonstrating that an increase in hand hygiene compliance rate by 45 percentage points to 60% could reduce the expected cases of gastrointestinal diseases among residents by 75% within 100 days [8].…”
Section: Introductionmentioning
confidence: 57%
“…Smith et al concluded that the average hand hygiene compliance rate of staff in long-term care facilities is only about 14.7% [6]. Similar results were found by Cordeiro et al, with an average hand hygiene compliance rate of 14.4%, varying with 4.8% before patient contact and 53.7% after patient contact, among other differentiation aspects [7]. Assuming these ndings, Assab and Temime (2016) incorporated real data on the spread of the Norovirus into a mathematical model, demonstrating that an increase in hand hygiene compliance rate by 45 percentage points to 60% could reduce the expected cases of gastrointestinal diseases among residents by 75% within 100 days [8].…”
Section: Introductionmentioning
confidence: 57%
“…Estudos demonstram que o momento de maior realização da higienização das mãos é após o contato com o paciente, esta prática é comum nos diferentes níveis de atenção à saúde. (24) Alguns autores, (25,26) ao interpretarem este comportamento, consideram que a preocupação do profissional em contaminar a si próprio se sobressai quando comparado ao medo de contaminar o paciente. Em outro estudo, foi apontado que um número significante (86,2%) de profissionais de enfermagem da APS reconhece que as mãos são uma das principais fontes de infecção cruzada.…”
Section: Discussionunclassified
“…Apesar da técnica de higiene de mãos ser difundida entre os profissionais de saúde, estudos apontam fragilidade na adesão e na qualidade desta prática (16)(17)(18) . Em um estudo realizado no departamento de emergência de um Hospital Universitário no Brasil, foram observados 59 profissionais de saúde, sendo a taxa de conformidade à HM de 54,2% (16) .…”
Section: Introdução Introduçãounclassified
“…Uma investigação realizada em uma Unidade de Terapia Intensiva Neonatal (UTIN) em um Hospital Universitário do Estado do Paraná com enfermeiros e técnicos de enfermagem, mostrou que a taxa de adesão à higienização das mãos foi de 55,4%, considerando 1096 oportunidades (18) . Já uma investigação conduzida na atenção domiciliar apontou que os profissionais de saúde não realizam a higiene das mãos seguindo os passos corretos e nem no tempo correto (17) .…”
Section: Introdução Introduçãounclassified